2008
DOI: 10.1152/physiolgenomics.00239.2007
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo gene expression signature of oxidative stress

Abstract: doi: 10.1152/physiolgenomics.00239.2007 You might find this additional info useful... Supplementary material for this article can be found at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(167 citation statements)
references
References 85 publications
6
158
0
3
Order By: Relevance
“…Several Nrf2 target genes, as well as other genes involved in apoptosis, DNA damage, oxidative stress, and protein folding, are induced by nifurtimox and nifurtimox plus TM combination treatment. These results are comparable to a study that investigated the in vivo gene expression of oxidative stress in mice treated with diquat, a redox cycler, and Sod1-/-mice (40). Similar to our results in nifurtimox and TM treated medulloblastoma cells, up-regulation in several antioxidant genes, including Srxn1, Gclc, Txn2, and HMOX-1, in SOD1-/-mice has been shown (40).…”
Section: Discussionsupporting
confidence: 91%
“…Several Nrf2 target genes, as well as other genes involved in apoptosis, DNA damage, oxidative stress, and protein folding, are induced by nifurtimox and nifurtimox plus TM combination treatment. These results are comparable to a study that investigated the in vivo gene expression of oxidative stress in mice treated with diquat, a redox cycler, and Sod1-/-mice (40). Similar to our results in nifurtimox and TM treated medulloblastoma cells, up-regulation in several antioxidant genes, including Srxn1, Gclc, Txn2, and HMOX-1, in SOD1-/-mice has been shown (40).…”
Section: Discussionsupporting
confidence: 91%
“…2 Shortest path co-citation network of genes for which transcript levels were significantly altered following extend fast generated using BiblioSphere software. following the extended fast, is increased in parallel with increased CDKN1A in response to oxidative and other cellular stresses (Han et al 2008) and in liver following treatment with glucocorticoids; hormones that help to regulate blood glucose during fasting (Wong et al 2010). Expression of clusterin at the level of mRNA is, at least in part, dependent on CDKN1A (Chen et al 2004).…”
Section: Effects Of Extended Fast On Pbmc Transcription Profilesmentioning
confidence: 99%
“…This activation results in upregulation of p53 and down-regulation of B cell lymphoma-2, ultimately leading to apoptotic cell death. [33][34][35] It has also been reported that H 2 O 2 is also capable of inducing the apoptosis of RGC-5 cells through the caspase-independent apoptotic pathway involving the upregulation of AIF and cleaved PARP proteins. 36) In our study, the levels of various apoptotic proteins in lysates harvested from control untreated cultures and cultures exposed to 800 μM H 2 O 2 in the presence or absence of R. verniciflua extract were determined by Western blot analysis for PARP, cleaved caspase-3, and caspase-9 (Fig.…”
Section: Effect Of R Verniciflua Extract On Lipid Peroxidationmentioning
confidence: 99%